Back Cover: Ion Intercalation Induced Capacitance Improvement for Graphene‐Based Supercapacitor Electrodes (ChemNanoMat 7/2016). Issue 7 (22nd June 2016) - Liu, Tianyu; Zhu, Cheng; Kou, Tianyi; Worsley, Marcus A.; Qian, Fang; Condes, Cecilia; Duoss, Eric B.; Spadaccini, Christopher M.; Li, Yat
Abstract : A facile electrochemical method was demonstrated to be effective in boosting the capacitance of graphene‐based electrodes, while retaining their excellent rate capability. This method involves two ion‐intercalation steps (lithium‐ion and perchlorate‐ion intercalation), followed by hydrolysis of perchlorate ion intercalation compounds. Lithium ion intercalation mainly leads to surface exfoliation, while the hydrolysis of perchlorate ion intercalation compounds functionalizes the graphene surface with oxygen moieties. The gravimetric capacitance of 3D printed graphene aerogels was almost double after the treatment, without significant decay in rate capability. More information can be found in the Communication by Y. Li et al. onpage 641 in Issue 7, 2016 (DOI:10.1002/cnma.201600107 ).